A Methods engineering study on Chemdis Manufacturing Corporation - Abella, Scott Alexander P. (College of Engineering, 2002)
Chemdis Manufacturing Corporation mainly produces PVC compounds and Plastic Colorants (PC), which are then used by most industrial or food enterprises as their raw materials. Their manufacturing plant consists of the production area, separated into the PVC Section and the PC Section, and the Warehouse.A methods engineering study was conducted with Chemdis as a means of identifying inefficiency which may hinder productivity within the company; and also to find feasible solutions to address the problems found. Supported by the Stream Diagnostic Chart, two main problems were identified : (1) Inefficient Plant Layout; and (2) Poor Organization of Raw Materials. Upon using other techniques, i.e. Procedure Charting, Forms Analysis, String Diagramming, and Simplified Systematic Layout Planning, the two main problems were further defined. Inefficient Plant Layout is mainly attributed to the fact that the warehouse is situated near the PC production area but too far from the PVC production area. Poor Organization of Raw Materials, on the other hand, resulted from an unorganized system of storing and recording the transport of goods to and from the warehouse. Through systematic analysis, the researchers were able to come up with feasible solutions to address the previous problems. In addressing the inefficiency of the plant layout, Alternative Layout II was proposed, wherein there are two separate warehouses, one for PVC and the other, PC. Results show that with this proposed layout, travel distances can be reduced. Additionally, the following alternatives were proposed : connect rooms of weighing section and mixing in the PC section; and situate Crushing near Extrusion in the PC section. Shorter travel distances would mean shorter travel times, and hence, productivity increases. Furthermore, the financial costs for Alternative Layout II is exceedingly lower than that of the other alternative. In addressing the poor organization of raw materials, the following alternatives deem to be beneficial and feasible at the same time : add more shelves, paint lines to clearly designate the floor space for various stacks of materials, label all storage spaces, and enforce the use of recording systems such as the whiteboard to keep track of the materials currently in the warehouse. Also, unused machines stored in the warehouse should be brought to the production plant once the new layout has been implemented.